Застосування методу зважених відхилів для визначення розподілу температур та деформацій радіаційної повзучості в пластинах - Бреславський, Дмитро Васильович; Татарінова, Оксана Андріївна; Чешко, Ксенія Федорівна (НТУ "ХПІ", 2017)
Статтю присвячено опису застосування методу зважених відхилів у формі методу Гальоркіна для розв’язання задач нестаціонарної теплопровідності та радіаційної повзучості у прямокутних пластинах. Розглянуто основні залежності, які застосова- но до отримання розв’язків даних задач. Задачу нестаціонарної теплопровідності зведено до послідовного розв’язання систем лінійних алгебраїчних рівнянь для коефіцієнтів при розкладенні функції температур у ряд за базисними функціями для різних моментів часу. Для розв’язання задачі радіаційної повзучості попередньо розглядається визначення функції переміщення у задачі згину прямокутної пластини при заданому перепаді температур на її сторонах. Наведено приклади розв’язання у вигляді розподілів температур та деформацій радіаційної повзучості за координатами та у різні моменти часу.

The paper is devoted to the description of the Weighted Residuals Method in Galerkin form for solution of the non-stationary heat transfer and irradiation creep problems in rectangular plates. The basic methods and dependencies were used for the solution of these problems are considered. The non-stationary heat problem is derived to sequential decisions of the systems of linear algebraic equations for the coefficients in expansions of temperature function in series on the basis functions for the different time moments. The problem of rectangular plate’s bending with specified temperature drops in its sides is preliminary solved in order to obtain the solution of irradiation creep problem. The stress tensor components were found in the plate’s points, are used in associated flow rule for the obtaining the components of creep irradiation strain tensor. The non-stationary heat transfer problem in quadratic area with boundary conditions of Newton and Diriclet types is considered as well as the calculated temperature distributions on co-ordinates in plane and time are presented. The irradiation creep of rectangular plate made from high resistant steel 15Х1М1Ф is considered. Obtained distributions of irradiation creep strains for three regarded values of temperature drops allow us to evaluate the plate deformation and service ability at different time moments.
Application of the method of weighted residuals for determining the distribution of temperatures and radiation creep strains in plates
Keywords: нестаціонарна теплопровідність; метод Гальоркіна; метод скінченних елементів; теорія тонких пластин; non-stationary heat transfer; irradiation creep; method of weighted residuals; Galerkin method